Building a Framework for Global Health Learning. (April 2015) - Watterson, Rita; Matthews, David; Bach, Paxton; Kherani, Irfan; Halpine, Mary; Meili, Ryan
<x xml:space="preserve">Abstract</x> Purpose This study set out to explore the current state of global health concentrations in Canadian medical schools and to solicit feedback on the barriers and challenges to implementing rigorous global health concentration programs. Method A set of consensus guidelines for global health concentrations was drafted through consultation with student and faculty leaders across Canada between May 2011 and May 2012. Drawing on these guidelines, a formal survey was sent to prominent faculty at each of the 14 English-speaking Canadian medical schools. A thematic analysis of the results was then conducted. Results Overall, the guidelines were strongly endorsed. A majority of Canadian medical schools have programs in place to offer global health course work, extracurricular learning opportunities, local community service–learning, low-resource-setting clinical electives, predeparture training, and postreturn debriefing. Although student evaluation, global health mentorship, and knowledge translation projects were endorsed as important components, few schools had been successful in implementing them. Language training for global health remains contested. Other common critiques included a lack of time and resources, and difficulties in setting standards for student evaluation. Conclusions The results suggest that these guidelines are appropriate and, at least for the major criteria, achievable. Although many Canadian schools offer individual components, the majority of schools have yet to develop formally structured concentration programs. By better articulating guidelines, a standardized framework can aid in the establishment and refinement of future programs.